Las transformaciones de las fuentes de derecho del trabajo: Una aproximación - Valdés Dal-ré, Fernando (Cuadernos de Relaciones Laborales, 2008)
The Spanish Labour Law system has been profoundly changed along the last three decades. These transformations have intensely and extendedly affected this system’s elements. The present article tries to offer a general perspective of those transformations, from a double point of view. First, and from the view of the Spanish Labour Law, the changes in the traditional model of regulation of the occupational relations are analyzed, paying special attention to the determinant factors of the folding of the governmental rules as well as the reorganization of the normative spaces of the law and the collective agreement. Second, and from the angle of the Social and Communitarian Law, the unstoppable and preoccupying advance of the soft law formulas and its effects on the project for social harmony are examined.